Status-seeking in criminal subcultures and the double dividend of zero-tolerance - Robert Dur; Joël van der Weele (Institute for the Study of Labor (IZA), 2011)
This paper offers a new argument for why a more aggressive enforcement of minor offenses (zero-tolerance) may yield a double dividend in that it reduces both minor offenses and more severe crime. We develop a model of criminal subcultures in which people gain social status among their peers for being tough by committing criminal acts. As zero-tolerance keeps relatively gutless people from committing a minor offense, the signaling value of that action increases, which makes it attractive for some people who would otherwise commit more severe crime. If social status is sufficiently important in criminal subcultures, zero-tolerance reduces crime across the board.
urn:nbn:de:101:1-201104113572
Keywords: K14; K42; 330; status concerns; street crime; subcultures; penalties; zero-tolerance; broken windows policing; Gewalt; Sozialer Status; Strafe; Kriminalität; Kriminalitätsökonomik; Rechtsdurchsetzung; Doppelte Dividende; Theorie